Analisa Tarif Layanan Kesehatan BPJS Kesehatan (INA-CBGS) dan Efisiensi Layanan Tahun 2017 - Hernowo Hernowo; Imam Wahyudi (Sekolah Pascasarjana Perbanas Jakarta, 2018)
This study is classified as ethnographic research is a type of research that is qualitative in assessing a problem. This study is in-depth and the researchers directly tangent to the problems studied by looking for informants from the environment involved with the problem. This study aims to determine whether Dr. Sismadi hospitals uses a method of unit cost calculation to determine its health care tariff, and how to set service rates to anticipate health BPJS patients with INA-CBGs tariff package The currently used clinical pathway is the concept of an integrated health service plan that summarizes every step taken in patients from entry to exit based on medical service standards, nursing care standards and other evidence-based healthcare standards (diagnostics) with measurable results in the long term certain time during the hospital. Activity based costing (ABC) is one method of unit cost calculation using activity as a reference in tariff determination. The purpose of this study is to provide an alternative in the preparation of outpatient and inpatient tariffs, as well as an alternative that can be used to manufacture tariff packages clinical pathway concept. The results showed that clinical pathways for BPJS health patients made by Dr. Sismadi hospitals still provide subsidies especially for surgical patients who use general anesthesia to BPJS patients, but for non-surgical cases with up to 3 (three ) day, the relative does not provide subsidies. The result of unit cost calculation with activity based costing (ABC) analysis for polyclinic outpatient and nursing service tariff shows a very varied result, so that the profit margin for each service tariff is very varied as well. The result of unit cost calculation shows that the hospital has not conducted maximum supervision on the cost of the activities of each service unit. The level of service efficiency by minimizing unit cost with the counselor on the quality and cost of BPJS patient health will be very beneficial for the hospital, so the possibility of subsidy or cost recovery can be minimized